Characterization of the breeding of guinea pigs in three provinces of the Cajamarca Region, Peru - Ortiz-Oblitas, Pedro (2021)
The present study aimed to characterize the guinea pig breeding system in three provinces of the Cajamarca Region, Peru. A structured survey was applied to 1231 producers (401 from Cajamarca, 360 from San Marcos and 470 from Cajabamba). The predominant production system is family-commercial (67% of producers). The Peru breed is preferred by producers, rearing the animals in pools. Most of the producers have less than 49 guinea pigs in a 0.5 to 5 ha land area. Alfalfa (Medicago sativa) being the forage most used in the feeding of guinea pigs. More than 80% of producers do not receive technical assistance and more than 87% are not part of a breeder association. In the sanitary characterization, 1 to 5 guinea pigs die per week and per producer, especially in the lactating class. The most reported disease is salmonellosis, which is identified by alterations in the liver.